Response of silage intake and milk production to replacement of barley by barley fibre derived from integrated starch-ethanol process - Huhtanen, Pekka; Ala-Seppälä, Hannele; Näsi, Matti (Agricultural and Food Science, 1988)
A duplicated 4 x 4 Latin Square experiment was conducted to determine the effects of a gradually increased level of barley fibre in the diet on ad libitum grass silage intake and milk production. Barley fibre is a fibrous ethanol-starch by-product (120 g crude protein, 550 g neutral detergent fibre (NDF) and 120 g starch/kg dry matter (DM)). The four supplements, given at the rate of 6.5 kg/d on DM basis, were barley (B) and barley of which 333 g/kg (BF), 667 g/kg (FB) and 1000 g/kg (F) were replaced by barley fibre. In addition the cows were given 1 kg of rapeseed meal and 0.25 kg of mineral mixture. As the proportion of barley fibre in the diet increased there was a linear (P